EXPLORATION OF THE HEALTH IMPACT OF DOUBLE BURDEN OF MALNUTRITION AMONG BANGLADESHI WOMEN - Hasan, Mehedi; Sutradhar, Ipsita (Public Health of Indonesia, 2017)
Double burden of malnutrition (DBM) is a growing concern, which refers to the coexistence of under nutrition and over nutrition within the same population. The recent increase in the prevalence of overweight and existing prevalence of underweight among Bangladeshi women clearly indicates the advent of a double burden of malnutrition in Bangladesh. Women's nutritional status is extremely important for a nation because it affects not only their own health but also the health of their children. Both under nutrition and over nutrition have the potential to make women vulnerable to various adverse health conditions as well as adverse obstetric experience and poor birth outcome. It is a timely need for policy makers of this country to come up with specific interventions for both undernourished and overnourished women considering all these factors.